Rapid formation of an ice doline on Amery Ice Shelf, East Antarctica - Philipp S. Arndt (10780465); Roland C. Warner (10780468); Helen A. Fricker (10780471); Susheel Adusumilli (10780474); Jonathan Kingslake (4614415); Julian J. Spergel (10780477) (2021)
Data and code for: Warner, R., Fricker, H., Adusumilli, S., Arndt, P., Kingslake, J., & Spergel, J. (2021). Rapid formation of an ice doline on Amery Ice Shelf, East Antarctica.